The ethical dilemma of citizenship by investment - Matsevich-Dukhan , Iryna Ja. (Journal of the Belarusian State University. Sociology, 2021)
The article reveals socio-philosophical basis for judging the phenomenon of the citizenship by investment in the creative society from the ethical perspective. Different ways of assessing the development of forms and content of the citizenship by investment as social and moral progress or regress are demonstrated. The paradoxical nature of the creative class choice between a sound possibility to invest into the beneficial citizenship and a necessity of its limitation from the moral point of European community view, expressed in public space and the EU official political discourse, is explicated.